Factors associated with coronary artery calcification in young female patients with SLE. Issue 9 (15th August 2003) - Manger, K; Kusus, M; Forster, C; Ropers, D; Daniel, W G; Kalden, J R; Achenbach, S; Manger, B
Abstract : Background: With improved survival rates of patients with systemic lupus erythematosus (SLE), damage such as accelerated atherosclerosis gains increasing importance. Objective: To identify the prevalence of coronary artery calcifications (CAC) in asymptomatic patients. Methods: Electron beam tomography (EBT) was performed in 75 female patients with SLE aged <50. The results were correlated with traditional and SLE related factors associated with CAC. 49 women with symptomatic coronary heart disease (CHD) and 279 women without CHD were also analysed. Results: Overall, 21/75 (28%) patients had CAC. Low HDL cholesterol levels <1.40 mmol/l (p=0.03, OR=1.8, 67% v 39%) and cigarette smoking (p=0.01, OR=5.7, 76% v 44%) were identified as factors associated with CAC. Hypertension and high cholesterol were more common in women with CHD (p<0.01) than in those without CHD. SLE related factors were proteinuria (1331 v 465 mg/day, p=0.02), impaired renal function (p=0.02, OR=2.6, 26% v 6%), and high C3 levels (p=0.04, OR=1.8, 65% v 38%). High C3 levels were also more common in symptomatic CHD (p=0.02). The prevalence of Sm antibodies was lower in patients with CAC (15% v 42%, p=0.03). In a multivariate analysis, cigarette smoking, reduced renal function, high C3, and a cumulative steroid dose above 30 g were the most important CAC associated factors in the lupus cohort. Conclusion: A subgroup of patients with SLE with CAC without any clinical symptoms of CHD was identified by EBT. Therefore, EBT is useful for assessing asymptomatic atherosclerosis in this group.